KAJIAN ETNOBOTANI TUMBUHAN PANGAN PADA MASYARAKAT SUKU MELAYU DI DESA BOYAN TANJUNG KABUPATEN KAPUAS HULU - Riza Linda, Rachmawati Satrima, Irwan Lovadi, (Jurnal Protobiont, 2015)
This research aimed to find out the types, parts of plant organ, processing methods and categories of utilization of food plants in the Malay Community of Boyan Tanjung Village, Kapuas HuluRegency. This study was conducted from March to April 2015 in Boyan Tanjung village and the Biology Laboratory of the Faculty of Mathematics and Natural Sciences, Tanjungpura UniversityPontianak. The study used a purposive sampling method. The research found 18 types belonging to 11 families. The most widely utilized family was the phyllanthaceae. Part of the plant widely utilized was the fruit. The processing methods of food plants were through direct consumption and after initial process. The categories of utilization of plants were divided into three i.e. as vegetable, snack and seasoning. The frequency of the highest citation in this research reached 100%. The Informant Agreement Ratio (IAR) value was the highest in the snack at 0.953.